APPLICATION BUILD SUPER BEAUTIFUL AND FULL ANIMATION WITH BORLAND DELPHI 7 - Harry Rizky Pribadi; Diyah Ruri Irawati, SKom, MMSI (Jurnal Sistem Informasi, 2010)
There are two things that must and should be considered in building an application, namely "How to create an application / program is running correctly (in accordance with our desires / our clients)" and "How to create the user interface of our application to be interesting, easy to use and beautiful as possible ". Why should an application look beautiful and attractive? This can be analogous to the case when you come to the store to buy dress shirts, all the clothes in the store of the same function, which is a cloth that covers your body. However, you certainly will not choose arbitrarily clothes (although all dress the same function), you would likely choose the clothes with the best of form and appearance and even the latest models. The same is also felt by your clients, they not only requires you to make a program that runs in accordance with their desired, but also applications that have attractive appearance and easy to use. They're not going to accept the application with a bad view, although the program has been running as they wish. Therefore, the authors create a writing entitled "Developing Applications Super Beautiful and Full Animation With Borland Delphi 7 which in scientific writing, the writer outlines the steps to build an interesting application using Borland Delphi 7 programming language with object-oriented and visual.